ANALISIS PERBEDAAN KINERJA AKIBAT DAMPAK PERUBAHAN TEKNOLOGI PADA UNIT INTERNATIONAL ROAMING PADA PERUSAHAAN TELEKOMUNIKASI PT XYZ - Tendy Arya Pranata; Arif Imam Suroso; Irman Hermadi (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
Technological changes impacts changes in behavior and work systems carried out by the organization. The company's investment in new technology should be able to increase revenue, but PT XYZ's revenue growth tends to be stagnant. Therefore, the central management designs an assessment measure that could be used to evaluate a unit's performance. This study aimed to analyze the differences in the international roaming unit's performance due to technological changes using the learning & development, customers, internal business processes, and financial approach. Also, it aimed to initiate recommendations to improve the performance of international roaming units due to technological changes. The data used were secondary data from internal companies, while the methods used were descriptive, Balanced Scorecard (BSC), and paired test. The result obtained was that security criteria had a real difference in the impact of technology adoption on the learning & development indicator. There were significant differences in the business process indicator due to technological change. There was no significant difference in the impact of technology adoption in terms of the customer and financial indicators. The international roaming unit needs to optimize technology adoption further. Keywords: balanced scorecard, organinternational roaming, technology adoption, performance, paired test